Theories of Regional Integration: Beyond Eurocentrism (2018)
This book analyzes the problem of Eurocentrism in the theoretical debates on regional in-tegration. Undoubtedly, the elaboration of the theory of integration, both in the field of economics and political science and international relations, has taken as a reference the experience of integration in Western Europe. Theories such as functionalism, neofunctio-nalism, intergovernmentalism or liberal intergovernmentalism emerged to explain European integration. The point is, on the one hand, that European theories have assumed the role of disciplining what is deemed an appropriate theorization of the phenomenon of integra-tion and, on the other hand, that these theories have been used to explain regional proces-ses beyond the old continent. This is the problem of Eurocentrism analyzed in this book. Although adopting a “reverse Eurocentrism”—that is, completely discarding European theo-retical inputs—is avoided, the book recovers the theoretical contributions from other re-gions in the world, particularly those in Latin America, such as Cepalist structuralism and the theory of autonomy. Also, it is argued that an uncritical and decontextualized application of European theory to integration processes that take place in other regions of the world may result in wrong explanations and conclusions.